Test and retest reproducibility of protocol to assess tactical behavior and offensive situations in Soccer - Oliveira , Lucas Martins; Moraes, José Cícero; Cunha-Neto, Pedro Sotero da; Denis, Ricardo; Foschiera, Diogo Bertella; Legnani, Rosimeide Francisco Santos; Legnani, Elto (Revista Brasileira de Educação Física e Esporte, 2023)
The purpose of this study is to analyze the reproducibility of offensive actions that result in goals in the Brazilian A Series Soccer Championship (2017). The sample was intentionally selected and comprised 10% (58) of effective offensive actions that resulted in a goal (n = 582) of the two best ranked teams. The selected offensive actions were obtained through images broadcasted on TV, and recorded and edited using the software Sportscode Version 11.0. The selection took place at two different moments, within an interval of 15 days, using the Assessment Protocol of Individual Tactical Performance, and we observed the following types of attacks and fundamental offensive tactical principles: offensive cover, mobility, space and penetration. The analysis was performed using descriptive statistics, weighted Kappa test and correlation coefficient (CCC), considering statistical significance of p <0.05. The tactical principles of Penetration, Offensive Cover, and Variability showed higher CCC values (0.98 to 1.00). In all tactical principles analyzed, the accuracy values were high (0.99 to 1.00). A 100% concordance was observed regarding the test and retest reproducibility of the attack methods (x2 = 116.0; p≤0.001). The reproducibility indicators of the assessment protocol of offensive actions were satisfactory, indicating their utilization in larger scale studies.